FACTORS AFFECTING THE LEARNING OUTCOMES IN BLENDED CLASSROOM BY SELECTED GRADE 12 HUMANITIES AND SOCIAL SCIENCES STUDENTS AT BESTLINK COLLEGE OF THE PHILIPPINES (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study examined the influential factors in blended learning among a cohort of 150 Grade 12 Humanities and Social Sciences students from Bestlink College of the Philippines. The research aimed to identify the factors influencing learning outcomes within the blended classroom environment. It included a review of relevant literature and an exploration of the Community of Inquiry model. The researcher used a cluster sampling technique to conduct this study. In terms of the assessment of Blended Classroom Factors, the overall weighted mean was 3.41, indicating strong agreement. Similarly, in Classroom Management, the overall weighted mean was 3.41, also indicating strong agreement. Regarding Learning Style Preference, the overall weighted mean was 3.35, again reflecting strong agreement. In terms of Traditional Classroom Factors within the Learning Environment, the overall weighted mean was 3.46, signifying strong agreement. Next, in the assessment of Resources, the overall weighted mean was 3.38, showing strong agreement. In the aspect of Motivation, the overall weighted mean was 3.45, indicating strong agreement. Lastly, in the evaluation of Online Classroom Factors, Student Engagement showed an overall weighted mean of 3.37, with strong agreement. In Pedagogical Design, the overall weighted mean was 3.44, again showing strong agreement. This research has the potential to enrich discussions on blended learning by providing valuable insights to enhance education. It can assist parents, schools, and researchers in making informed decisions and creating more adaptable learning environments.
Keywords: learning outcomes; blended learning